2018
DOI: 10.1080/02648725.2018.1471642
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs in virology: an RNA genomics approach

Abstract: Advances in sequencing technologies and bioinformatic analysis techniques have greatly improved our understanding of various classes of RNAs and their functions. Despite not coding for proteins, non-coding RNAs (ncRNAs) are emerging as essential biomolecules fundamental for cellular functions and cell survival. Interestingly, ncRNAs produced by viruses not only control the expression of viral genes, but also influence host cell regulation and circumvent host innate immune response. Correspondingly, ncRNAs prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…[1][2][3] However, recent studies have shown that less than 2% of the human genome is coding genes, and over 90% of the genes are noncoding genes that play regulatory roles in most systems. 4 Noncoding RNA (ncRNA) can regulate gene expression at different levels such as epigenetic modification, transcription and posttranscription. [5][6][7] NcRNAs can be divided into short ncRNAs, midsize ncRNAs and lncRNAs according to the length of their nucleotides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] However, recent studies have shown that less than 2% of the human genome is coding genes, and over 90% of the genes are noncoding genes that play regulatory roles in most systems. 4 Noncoding RNA (ncRNA) can regulate gene expression at different levels such as epigenetic modification, transcription and posttranscription. [5][6][7] NcRNAs can be divided into short ncRNAs, midsize ncRNAs and lncRNAs according to the length of their nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that the carcinogenic effects of genes are mainly exerted by transcription and protein encoding of genes . However, recent studies have shown that less than 2% of the human genome is coding genes, and over 90% of the genes are noncoding genes that play regulatory roles in most systems . Noncoding RNA (ncRNA) can regulate gene expression at different levels such as epigenetic modification, transcription and posttranscription .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the function of the RNA genome as a noncoding RNA genome has gained increasing attention in the last decade and has contributed to the understanding of complex co-evolutionary processes between viruses and host cells. [137]. However, the role of secondary RNA structures in viral biology is mainly known in canonical processes such as viral replication [138].…”
Section: A Tropical Case: Dengue Virus (Denv)mentioning
confidence: 99%
“…LncRNAs cannot code for protein, but can modulate gene expression at epigenetic (e.g., DNA methylation, histone modification), transcriptional (e.g., recruitment of transcription factors), and post-transcriptional (e.g., regulation of miRNA and mRNA stability) levels [ 97 ]. An increasing number of studies have demonstrated deregulation or aberrant expression of miRNAs and lncRNAs in a variety of diseases, including infection disease [ 98 ]. Mane studies have shown that miRNAs and lncRNAs play a role a direct role in the virus life cycle [ [99] , [100] , [101] ].…”
Section: Non-coding Rnas In Covid-19mentioning
confidence: 99%
“…The involvement of these molecules in the escape of the virus from the action of the host immune response is a critical factor that requires in-depth analysis in the development of anti-COVID-19 vaccines and gene therapy approaches. The study of such important post-translational viral regulators has great diagnostic and therapeutic potential for COVID-19 infection [ 97 , 98 ].…”
Section: Limitations Of Mirnas-lncrnas-based Therapeutic and Diagnost...mentioning
confidence: 99%